The graphic section of the company C. Furest & Cia, the Funtimod foundry and the modern types - R. Aragão, Isabella; Azerêdo, Eduardo; da Costa, Dayane (InfoDesign, 2023)
Founded in Rio de Janeiro, the company C. Fuerst & Cia began its journey in 1920 with great emphasis on its work in the graphic and typographic field, the main focus of this research. The historical study demonstrates the importance of C. Fuerst in importing machinery for the graphic arts, with emphasis on offset printers, in addition to its contribution in the typographic area by representing the material of the German foundry D. Stempel and bringing up the conceptualization of modern types. Having Funtimod – Fundição de Tipos Modernos as the main reference in the field of typography in Brazil in the 20th century, we propose to place the typographic collections of the company and the foundry side by side, making a survey of similarities and differences. Through this, we conclude that only the studied foundry has a collection consistent with modernity of the time.